Does the economy really matter for satisfaction with democracy? Longitudinal and cross-country evidence from the European Union. (June 2016) - Quaranta, Mario; Martini, Sergio
Abstract: Research focusing on the relationship between the economy and satisfaction with democracy often presents mixed results. This article argues that this uncertainty is mainly due to model specification, number of surveys and measurement. After discussing why the role of the economy should not be overlooked, by using an empirical strategy that applies Bayesian cross-classified mixed models to 572 national surveys in 28 European countries from 1973 to 2013 drawn from the Eurobarometer, it is shown that objective macro-economic indicators and a subjective indicator seem to substantially affect citizens' satisfaction with democracy in Europe. The findings are robust when controlling for various institutional and political variables and using alternative model specifications. Highlights: This article links satisfaction with democracy with the economy. Previous research is inconclusive about their association. The article proposes an empirical strategy to solve this uncertainty. 572 Eurobarometer surveys of 28 European countries (1973–2013) are used. Bayesian mixed models show that democratic satisfaction varies with economic conditions.